In-chip critical plasma seeds for laser writing of reconfigurable silicon photonics systems - Andong Wang; Amlan Das; Vladimir Yu Fedorov; Pol Sopeña; Stelios Tzortzakis; David Grojo (Nature Communications)
Abstract Ultrafast laser three-dimensional writing has made breakthroughs in manufacturing technologies. However, it remains rarely adopted for semiconductor technologies due to in-chip propagation nonlinearities causing a lack of controllability for intense infrared light. To solve this problem, plasma-optics concepts are promising since ultrashort laser pulses, even if inappropriate for direct writing, can readily inject high-density free-carriers inside semiconductors. To achieve highly localized and reliable processing, we create plasma seeds with tightly focused pre-ionizing femtosecond pulses. We show how critical density conditions can be used for extremely confined energy deposition with a synchronized writing irradiation and create ~ 1-µm-sized isotropic modifications inside silicon. Drastic improvement is also found on the material change controllability leading to unique demonstrations including rewritable optical memories (>100 writing/erasure cycles) and graded-index functionalities. By solving its controllability issues with critical plasma seeds, we show the potential of ultrafast laser writing for flexible fabrication of reconfigurable monolithic silicon-based optical devices.